Modified-TAM Analysis of the Implementation of the e-Hospital System on Polyclinic Service - Pratama, Devina Gracia; Prasetyo Agung, Ignatius Wiseto; Purwadhi, Purwadhi (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2022)
Background: Technology in the field of health services allows an individual to get a productive life and a longer life expectancy. The purpose of this study was to provide describe of obstacles in the implementation of the e-Hospital system, especially EMR services at the Dermatology & Venereology (DV) Polyclinic